The Influence of Individual Adaptability and Perceived Organizational Support on Performance Through Organizational Commitement in The Family Support Team in Lamongan Regency - Kurniasari, Sinta; Brahmasari, Ida Aju; Ardiana, I Dewa Ketut Raka (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The Family Support Team is an organization consisting of Midwives, PKK Cadres and Family Planning Cadres, duty for carrying out family support in reducing the prevalence of stunting. This research aims to prove and analyze the influence of individual adaptability and perceived organizational support on performance through organizational commitment in the Lamongan Regency Family Support Team. The approach in research uses a quantitative approach. Total sample was 354 respondents from a total population of 3.108 people, using proportional random sampling technique. The data collection technique using questionnaire via Google form which was distributed to members of the Family Support Team in Lamongan Regency. Testing was carried out using the SEM-AMOS statistical technique on the 5 proposed hypotheses. The results of this research show that: (1) Individual adaptability has significant effect on organizational commitment, (2) Individual adaptability has significant effect on member performance, (3) Perceived organizational support has significant effect on organizational commitment, (4) Perceived organizational support has significant effect on member performance, (5) Organizational commitment has significant effect on member performance of Family Assistance Team members in the Regency Lamongan.